PENGARUH BUDAYA ORGANISASI DAN ROTASI PEKERJAAN TERHADAP KINERJA PEGAWAI PADA DINAS SOSIAL PROVINSI SUMATERA BARAT - Doni Marlius; Lafenia Mayang Sari (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of organizational culture and job rotation on employee performance at the social services of the province of West Sumatra, this research is a quantitative study, the sampling method uses total sampling with a total of 60 respondents. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that organizational culture has no positive and significant effect on employee performance with a t-count value smaller than t-table (-1.018 < 1.671), job rotation has a positive and significant effect on employee performance with a higher t-count value from t-table (3.639>1.671).